A Review of Online Social Network Hypotheses for Business Continuance Intention (International Journal of Scientific Research and Management (IJSRM), 2017)
Online Social Networks (OSN) have come butcould not survive, yet the explosion of business activities on such platforms continuous to surge high, giving advantage to the bold entrepreneurs. It is therefore a practical requirement that practitioners and researchers understand the key determinants of costumers’ online social network business activities and continuance intention. An exploratory literature research to examine OSN continuous intention of business participants on OSN revealed that the practice of doing business on social network has come to stay and the following factors are the likely drivers for this new business model: perceived trust, perceived ease of use, confirmation, Habit, social norm, perceived behavioural control, expected benefit and satisfaction are the most probable factor that can lead to online social network (OSN) continuance intention.This paper throws light on the above listed OSN influencing factors and the likely emanating model.